Conformal growth of anodic nanotubes for dye-sensitized solar cells : part II. nonplanar electrode - Sun, Lidong (2014)
Anodic titania nanotube array features highly ordered alignment as well as porous nature, and exhibits intriguing properties when employed in a variety of applications. All these profit from the continuous efforts on controlling the nanotube configurations. Recently, nonplanar electrodes have also been used to grow the nanotubes besides the conventional planar counterparts. As such, it is of great interest and significance to complete a picture to link the nanotubes grown on planar and various nonplanar electrodes for a comprehensive understanding of nanotube growing manners, in an attempt to boost their future applications. In the first part of this review, planar electrodes are focused with regard to nanotube growth and application in dye-sensitized solar cells. In this part, the nanotubes grown on patterned or curved surfaces are discussed first with reference to a similar structure of alumina nanopores, which are subsequently used to mirror the growth of nanotubes on cylindrical electrodes (i.e., titanium wires or meshes). The last section focuses on titanium tubular electrodes which are attractive for thermal fluids in view of the drastically reduced thermal conductivity in the presence of anodic nanotubes. As a recent hot topic, wire-shaped dye-sensitized solar cells are deliberated in terms of cell structure, efficiency calculation, merits, challenges and outlook.